Upaya International Labour Organization (ILO) Melalui IPEC Dalam Menanggulangi Masalah Hak Pekerja Anak Pada Sektor Pertambangan di Mongolia Tahun 2005-2010 - Aanval, Yelestisky; Priadarsini, Ni Wayan Rainy; Widya Nugraha, A.A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT Mongolia is a developing country with a high mining potential, this sector in Mongolia still involves manual processes. This study discusses the ILO's efforts through the IPEC programme in tackling child labor issues in Mongolia. The deprivation of children's rights and operational function of international organization can analyze how i ILO help the state to overcome the problem of child labour by looking at the missing rights of child which is considered one form of hazardous work for children under 18 years. The research method used in this research is descriptive qualitative which explains about child labour in Mongolia by looking at ILO’s effort in tackling the problem of child labour. With programs designed by the ILO, the Mongolian government and ILO improving the quality of education, raising awareness of the child labour, making policies to regulate child labor, and carrying out various controls on child labor Keywords: ILO IPEC Project, Child Mining, Child rights, Mongolia